Spermatogonial Stem Cell-Based Therapies: Taking Preclinical Research to the Next Level - Sanou, Iris; van Maaren, Jillis; Eliveld, Jitske; Lei, Qijing; Meißner, Andreas; de Melker, Annemieke A.; Hamer, Geert; van Pelt, Ans M. M.; Mulder, Callista L. (Frontiers in Endocrinology, 2022)
Fertility preservation via biobanking of testicular tissue retrieved from testicular biopsies is now generally recommended for boys who need to undergo gonadotoxic treatment prior to the onset of puberty, as a source of spermatogonial stem cells (SSCs). SSCs have the potential of forming spermatids and may be used for therapeutic fertility approaches later in life. Although in the past 30 years many milestones have been reached to work towards SSC-based fertility restoration therapies, including transplantation of SSCs, grafting of testicular tissue and various in vitro and ex vivo spermatogenesis approaches, unfortunately, all these fertility therapies are still in a preclinical phase and not yet available for patients who have become infertile because of their treatment during childhood. Therefore, it is now time to take the preclinical research towards SSC-based therapy to the next level to resolve major issues that impede clinical implementation. This review gives an outline of the state of the art of the effectiveness and safety of fertility preservation and SSC-based therapies and addresses the hurdles that need to be taken for optimal progression towards actual clinical implementation of safe and effective SSC-based fertility treatments in the near future.